Internalization of Islamic Moral Values in Early Childhood Through the Exemplary Model of Prophet Muhammad at Early Childhood Education Centers in Central Bengkulu - Silvia Silvia; Alfauzan Amin; Ramedlon Ramedlon; Evi Selva Nirwana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study was motivated by the importance of internalizing Islamic moral values from an early age to build children’s character based on Islamic teachings. The research problems focused on the forms of internalization of Islamic moral values through habituation based on the exemplary conduct of Prophet Muhammad (PBUH) and the supporting and inhibiting factors at PAUD Kasih Bersama Central Bengkulu. This study used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The results showed that the internalization of Islamic moral values was carried out through habituation activities such as greetings, smiling, daily prayers, honesty, politeness, compassion, and helping others based on the example of Prophet Muhammad (PBUH). Supporting factors included consistent habituation, interesting learning methods, and a conducive school environment. Inhibiting factors included the influence of gadgets, differences in parenting styles, and differences in children’s characteristics. Habituation based on the exemplary conduct of Prophet Muhammad (PBUH) had a positive impact on children’s moral development.